2020
DOI: 10.3390/ijerph17186805
|View full text |Cite
|
Sign up to set email alerts
|

Differential Experiences of Mental Health among Trans/Gender Diverse Adults in Michigan

Abstract: Transgender and gender diverse individuals experience high rates of health disparities, as compared with their cisgender (non-transgender) counterparts. One area in which these disparities is most grave is that of mental health, with some studies indicating transgender and gender diverse individuals as having a 40% rate of lifetime suicide attempts and similarly high rates of depression, anxiety, and suicidal ideation. These rates vary further within this population, with differential rates seen across sociode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 77 publications
(97 reference statements)
2
6
0
Order By: Relevance
“…Regarding the second aim of the study, our results corroborated the different rates of prevalence of distal and proximal stressors across different minority sexual orientations and gender identities (Kattari et al, 2020;Schmitz et al, 2020;Shramko et al, 2018;Su et al, 2016). In line with prior literature, our findings suggested that TGD and sexual orientations other than gays or lesbians face greater exposure to heterosexism and cissexism.…”
Section: Article In Presssupporting
confidence: 89%
See 2 more Smart Citations
“…Regarding the second aim of the study, our results corroborated the different rates of prevalence of distal and proximal stressors across different minority sexual orientations and gender identities (Kattari et al, 2020;Schmitz et al, 2020;Shramko et al, 2018;Su et al, 2016). In line with prior literature, our findings suggested that TGD and sexual orientations other than gays or lesbians face greater exposure to heterosexism and cissexism.…”
Section: Article In Presssupporting
confidence: 89%
“…For instance, bisexual men and women have been proven to be at a greater risk of proximal stressors, such as isolation, while gay men and lesbian women are at a greater risk of exposure to distal minority stressors, such as discrimination and rejection (Mereish et al, 2017). Moreover, higher levels of discrimination and distress have been found in transgender and gender diverse individuals (TGD) when compared with cisgender LGB and heterosexual individuals (Kattari et al, 2020;Su et al, 2016;Valentine & Shipherd, 2018;Wiepjes et al, 2020). Additionally, lower levels of discrimination and victimization seem to be common among urban LGBTQ+ individuals when compared to those from suburban and rural backgrounds (Morandini et al, 2015;Shramko et al, 2018).…”
Section: Minority Stress and Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings follow extant research that found in-group differences within the TGD population in mental health (Kattari et al 2020), forced sex (Atteberry-Ash et al 2020), intimate partner violence (Walls et al 2019), and access to health care (Kattari et al 2019). Collectively, this demonstrates the need for surveys and forms to move away from the "man/woman/transgender" model that is so common and toward ones that allow for more nuance both within and across gender.…”
Section: Discussionsupporting
confidence: 84%
“…The sample for this paper was limited to those self‐reporting having ever been sexually active (yes/no). As described elsewhere [ 30 , 31 ], participants were recruited using convenience methods both online (e.g. Facebook) and in‐person (e.g.…”
Section: Methodsmentioning
confidence: 99%